Analysis and research of industrial value chain optimization model based on energy internet environment - Shaoyang Yin; Xiaohua Yang; Qi Xu; Guangjie Liu (Sustainable Energy Research)
Abstract This study conducts an in-depth analysis of the optimization model of the industrial value chain under the Energy Internet environment, and provides strong data support for the optimization of the industrial value chain through the presentation of specific data. Research data show that the application effect of Energy Internet in the industrial value chain is remarkable. In terms of energy consumption, the implementation of Energy Internet technology has resulted in a notable 25% reduction in the average energy consumption cost across the industrial value chain. Specifically, considering a prominent manufacturing enterprise as a case study, the introduction of the Energy Internet has led to a substantial 30% decline in its energy consumption cost, thereby enhancing the company's cost control capabilities significantly. In terms of production efficiency, the utilization of Energy Internet technology has brought forth remarkable improvements. According to statistics, the production efficiency of enterprises implementing Energy Internet technology has increased by an average of 18%. Especially in the manufacturing industry, some leading companies have realized the intelligence and automation of production processes through the Energy Internet, and the increase in production efficiency has reached more than 25%. Based on these specific data, this study builds an industrial value chain optimization model. The proposed model takes into account the multifaceted impact of the Energy Internet on each link of the industrial value chain, achieving comprehensive optimization by rationalizing resource allocation, enhancing energy utilization efficiency, and mitigating operational expenses. The simulation data reveal that, guided by this optimization model, enterprises can achieve a marked enhancement in their overall competitiveness. Furthermore, it is anticipated that this approach will potentially lead to a further 10% improvement in energy efficiency and a reduction of 15% in operational costs. In addition, this study also combines the actual cases of many industries to verify the optimization model. Following the implementation of the optimization model, the participating case companies have exhibited remarkable outcomes. Specifically, they have achieved an average reduction of 22% in energy costs and a corresponding increase of 17% in production efficiency. These findings further corroborate the efficacy of the optimization model.